Speed - Manning, S.
This is the third article in my training series after endurance and strength. Speedwork is certainly the most complex of all the components of a training program. There are many different types of sessions and different ways of running them. Basic training principles are consistent for individuals but each runner's innate ability makes them respond very differently. THE VALUE OF SPEEDWORK The importance of speedwork in adapting to progressive training loads can not be underestimated. Speedwork most closely simulates a race itself. Because of the level of intensity it is speedwork which determines and controls race fitness. Being `FIT` is not the same as being able to race fast. A good motto is if you want to race fast then train fast. Train slow and all you will be able to do is run slow. Speedwork actually improves recovery and decreases injury risk. It does this mainly because of the big increase in production of Human Growth Hormone after intense training. Other advantages for injury prevention are improved flexibility and increased strength out of the normal range of motion. Running form is also better when running faster so biomechanical problems are lessened and sometimes cured. I believe that the most important benefit of speedwork is greater mental strength and confidence. Training in a group at race pace is good practice for controlling excitement in races. Developing pace judgement is as important as the physical benefits of speedwork. There is no better skill going into a race than knowing how to run the right pace regardless of what speed everyone else is running. Most people go out fast then crash and burn. Even pace will guarantee you a better placing as well as the best time of which you are capable. Speedwork is the way to achieve perfect pace judgement for races.